RADIOGRAPHIC CHARACTERISTICS THE EFFECTIVENESS OF TREATMENT CAT WITH PURULENT OSTEOMYELITIS - Собчишина, Т. М. (Scientific Progress & Innovations, 2013)
The data of X-ray after the application of granular implants Biomin-hTlS of bone defects. Found that the use of these implants leads to activation of reparative osteogenesis and play anatomic shape and bone structure. Radiologically detected and describes the main tissue changes characteristic of osteomyelitis. It is shown that the X-ray study allows to diagnose osteomyelitis at an early stage and be an effective treatment.